A Prospective, Placebo‐Controlled Pilot Evaluation of the Effect of Omeprazole on Serum Calcium, Magnesium, Cobalamin, Gastrin Concentrations, and Bone in Cats - Gould, E. (J Vet Intern Med, 2016)
BACKGROUND: Chronic proton pump inhibitor administration has been associated with electrolyte and cobalamin deficiency, disrupted bone homeostasis, hypergastrinemia, and rebound acid hypersecretion in humans. It is unknown if this occurs in cats. OBJECTIVES: Prolonged oral omeprazole results in altered bone mineral density or content, serum calcium, magnesium, cobalamin, and gastrin concentrations in healthy cats. ANIMALS: Six healthy adult DSH cats. METHODS: In a within subjects, before and after design, cats received placebo followed by omeprazole (0.83–1.6 mg/kg PO q12h) for 60 days each. Analysis of serum calcium, magnesium, cobalamin, and gastrin concentrations was performed on days 0, 30, and 60. Bone density and content were evaluated on days 0 and 60 of each intervention. Continuous data were analyzed using a two‐way ANOVA (α = 0.006). On day 60 of omeprazole administration, continuous intragastric pH monitoring was performed in 2 cats to evaluate the effects of abrupt withdrawal of omeprazole. RESULTS: No significant changes were detected between treatments for any variables, except serum gastrin, which was significantly higher during omeprazole treatment in comparison to placebo (P = 0.002). Evidence of gastric hyperacidity was seen in both cats in which intragastric pH monitoring was performed following cessation of omeprazole. CONCLUSIONS AND CLINICAL IMPORTANCE: Although further studies with larger populations of cats will be needed to draw any definitive conclusions, these preliminary results suggest that prolonged PPI treatment results in hypergastrinemia and abrupt PPI withdrawal might result in RAH in cats.